Application of fuzzy logic and social media on flood hazards early warning system - Evelina Ginting; Nyanyu Latifah Husni; Tresna Dewi; Ade Silvia Handayani; Muhamad Rizki Harahap (Department of Electrical Engineering Education, Faculty of Teacher Training and Education, 2018)
This research aims to reduce losses that arise because of the flood in a way create a notifier flooding as flood detection. Sensors Ultrasonic sensors measure distance as can be applied as a water level detector, while the sensors used to detect flow velocity of the water flow. Research methods used in the form of literature reviews and making hardware and software using sensors SR04-HC. Applica-tion of fuzzy logic is used as a data processing of the ultrasonic sensor and flow sensor. Fuzzy logic will result in a decision on environmental conditions. With the decision made by fuzzy logic, early warning against the danger of flooding, in the form of an alarm and display the text that indicates a likelihood of flooding, as well as to social media news delivery can be carried out.